Morphology of the preimaginal stages of Carcinopyga lichenigera C. Felder & R. Felder, 1874 (Lepidoptera: Erebidae: Arctiinae) - Spitsyn, Vitaly M.; Evdoshenko, Sergey I.; Masroor, Rafaqat; Tiwari, Sundar; Spitsyna, Elizaveta A. (Acta Biologica Sibirica, 2025)
In this paper, we describe the preimaginal stages of Carcinopyga lichenigera C. Felder & R. Felder distributed in the mountain regions of eastern Afghanistan, northern Pakistan, and northwestern India (Ladakh; Jammu and Kashmir). Additionally, we illustrate adults of both sexes as well as their genitalia. Illustrations of female genitalia are provided for the first time.